Rapid Detection of Candida albicans by Polymerase Spiral Reaction Assay in Clinical Blood Samples - Jiang, Xiaoqun; Dong, Derong; Bian, Lihong; Zou, Dayang; He, Xiaoming; Ao, Da; Yang, Zhan; Huang, Simo; Liu, Ningwei; Liu, Wei; Huang, Liuyu (Frontiers in Microbiology, 2016)
Candida albicans is the most common human yeast pathogen which causes mucosal infections and invasive fungal diseases. Early detection of this pathogen is needed to guide preventative and therapeutic treatment. The aim of this study was to establish a polymerase spiral reaction (PSR) assay that rapidly and accurately detects C. albicans and to assess the clinical applicability of PSR-based diagnostic testing. Internal transcribed spacer 2 (ITS2), a region between 5.8S and 28S fungal ribosomal DNA, was used as the target sequence. Four primers were designed for amplification of ITS2 with the PSR method, which was evaluated using real time turbidity monitoring and visual detection using a pH indicator. Fourteen non- C. albicans yeast strains were negative for detection, which indicated the specificity of PSR assay was 100%. A 10-fold serial dilution of C. albicans genomic DNA was subjected to PSR and conventional PCR to compare their sensitivities. The detection limit of PSR was 6.9 pg/µl within 1 h, 10-fold higher than that of PCR (69.0 pg/µl). Blood samples (n=122) were collected from intensive care unit and hematological patients with proven or suspected C. albicans infection at two hospitals in Beijing, China. Both PSR assay and the culture method were used to analyze the samples. Of the 122 clinical samples, 34 were identified as positive by PSR. The result was consistent with those obtained by the culture method. In conclusion, a novel and effective C. albicans detection assay was developed that has a great potential for clinical screening and point-of-care testing.